Physics of Black Holes: A guided tour - Papantonopoulos, Eleftherios (Springer, 2017)
Black holes are the most mysterious and fascinating objects of our universe. They were predicted by the Einstein’s theory of general relativity and their existence is the triumph of this theory. A possible detection of gravitational waves by the gravity experiments will give vital information on the nature and properties of black holes. On the other hand, the recent advances in string theory offered a new understanding of the classical and quantum properties of black holes. This book is a guided tour, by world experts, on the new developments in the physics of the black holes.